2020
DOI: 10.3390/cryst10020075
|View full text |Cite
|
Sign up to set email alerts
|

The Phase Transition and Dehydration in Epsomite under High Temperature and High Pressure

Abstract: The phase stability of epsomite under a high temperature and high pressure were explored through Raman spectroscopy and electrical conductivity measurements in a diamond anvil cell up to ~623 K and ~12.8 GPa. Our results verified that the epsomite underwent a pressure-induced phase transition at ~5.1 GPa and room temperature, which was well characterized by the change in the pressure dependence of Raman vibrational modes and electrical conductivity. The dehydration process of the epsomite under high pressure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…However, the water molecules create a different configuration, which leads to deliquescence and the formation of the mixed phase of the crystal. As per the previous reports, hydrated sulfates undergo dehydration reactions under high-temperature and pressure conditions that result in the formation of lower hydrate structures. ,,,, However, in the present case, we have not observed such a dehydration process in MgSO 4 ·7H 2 O.…”
Section: Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the water molecules create a different configuration, which leads to deliquescence and the formation of the mixed phase of the crystal. As per the previous reports, hydrated sulfates undergo dehydration reactions under high-temperature and pressure conditions that result in the formation of lower hydrate structures. ,,,, However, in the present case, we have not observed such a dehydration process in MgSO 4 ·7H 2 O.…”
Section: Results and Discussionsupporting
confidence: 78%
“…Gromnitskaya et al have performed a high-pressure neutron powder diffraction study of crystalline MgSO 4 ·7H 2 O and found a series of phase transitions at 1.4, 1.6, and 2.5 GP . Very recently, Yang et al have carried out the combined high-pressure and high-temperature experiments on the titled crystal and found three steps of phase transitions with respect to temperature, and they also observed that the dehydration rate is increased with the increasing pressure range …”
Section: Introductionmentioning
confidence: 99%
“…By virtue of these electrical, spectroscopic, and theoretically calculating studies, a series of physiochemical behaviors of the pressure-induced structural phase transformation and dehydration effect on the hydrous minerals (e.g., kaolinite, epsomite, goethite, chalcanthite, gypsum, etc.) have already studied from Dai Lidong's high-pressure research group in HTHPSEI, at the Institute of Geochemistry, Chinese Academy of Sciences [73][74][75][76][77]. In addition, some important semiconducting materials including the binary metallic oxides, AB-type structural layered metallic compounds, AB2-type structural transition-metal dichalcogenides (TMDs), and ABO3type structural perovskite compounds are paid attention in regards to their structural phase transition, amorphization, and metallization, and investigated under conditions of HP-HT conditions in detail [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: High-pressure Apparatus For the Ec Measurements And Ft-ir Observationmentioning
confidence: 99%
“…One of the methods that can be used to obtain new polymorphs is exposing the molecular crystals to high-pressure in order to induce the phase transition [1]. Many studies deal with the experimental pressure-induced polymorphic transformations in molecular solids [2][3][4], in some cases the high-pressure polymorph may have the same space group symmetry as the original ambient-pressure form and even be isostructural with it, which is defined as isosymmetric phase transition [5,6]. However, in most cases the polymorphic phase transition is accompanied with the change of not only cell dimensions but also the crystal space group.…”
Section: Molecular Modeling Of Pressure Induced Phase Transitionmentioning
confidence: 99%